2015
DOI: 10.15171/jarcm.2015.016
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the correlation of trauma severity, blood sugar level, and neurologic outcomes in traumatic spinal cord injury patients

Abstract: Trauma, due to stimulating stress responses like hormones, increases the blood sugar level (BS level). 1 by inducing neurohormonal reactions, acute trauma leads to changes in carbohydrate, protein, and fat metabolism. As it was said, by releasing special cytokines and body defense regulating hormones, trauma results in increased BS level (hyperglycemia), which significantly affects body function and treatment process. In fact, hyperglycemia is a compensatory response of the body against trauma and stress. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Liu-DeRyke et al (30) shown that the strongest predictive value for predicting outcome is peak random blood sugar within the first twenty-four hours following injury and admission. In patients who have experienced a TBI, a high blood glucose level is a predictor of early mortality and a worse result (31,32) .…”
Section: Discussionmentioning
confidence: 99%
“…Liu-DeRyke et al (30) shown that the strongest predictive value for predicting outcome is peak random blood sugar within the first twenty-four hours following injury and admission. In patients who have experienced a TBI, a high blood glucose level is a predictor of early mortality and a worse result (31,32) .…”
Section: Discussionmentioning
confidence: 99%
“…Among trauma patients, the association of outcome with hyperglycemia has been studied extensively in major trauma patients, in whom it portends a poorer prognosis (Gore et al, 2002;Yendamuri et al, 2003;Simsek et al, 2014;Torbati et al, 2015). This finding is attributed to the fact that trauma patients present with a hypermetabolic response to injury that is driven by an increase in the activity of the hypothalamus and sympathetic nervous system that leads to an increased release of ACTH, catecholamine, and glucagon.…”
Section: Discussionmentioning
confidence: 99%
“…Even though stress-induced hyperglycemia has been associated with an increase in morbidity and mortality among patients with major trauma (Simsek et al, 2014;Torbati et al, 2015), the available literature on stress-induced hyperglycemia post-trauma has been conducted in the developed world (Gore et al, 2002;Yendamuri et al, 2003;Sung et al, 2011;Simsek et al, 2014;Torbati et al, 2015). This study is distinct from other reports in the literature, for its setting in a developing country with unique characteristics, challenges, and the largest burden of trauma.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fourth, the severity and level of SCI are wellrecognized prognostic factors for recovery after traumatic SCI and, hence, both factors should be considered in the data analyses as potential confounders. 36 Further, Torbati and associates 37 reported that at an acute care spine trauma in Iran individuals with more severe SCI had higher glycemic levels on admission.…”
Section: Hyperglycemia and Recovery After Cns Injurymentioning
confidence: 99%